Domestic Hot Water Storage Tank Design using Low-Cost Materials - Mantilla López, Juan Alberto; Casallas Rodríguez, Mario Alexander (Ingeniería Solidaria, 2016)
Introduction: this article is the result of the research “Design and construction of solar heaters with reusable material”. The research was conducted by the research seedbed sea, part of the research group of alternative power GIEAUD of the District University Francisco José de Caldas, from November 3, 2014 to April 10, 2015. Methodology: the study describes mathematical analysis, selection of materials (both for the insulator and the tank body), simulation of hydrostatic behavior, construction processes based on the norm ASME, section VIII, test runs, and thermal assessment. Results: the solar collector (built by the students of the sea seedbed) and the tank built by the authors of this report were installed on the gymnasium’s terrace of the Technical Faculty of the District University Francisco José de Caldas. The tank was assessed to demonstrate its efficiency in conserving temperature levels and functioning as a solar heater. Conclusion: the experience acquired in creating and developing the tank and the assemblage of solar collectors confirms the convenience to pursue research on more elaborate methods that will allow the improvement of operations and usage of new materials in the design, manufacture and evaluation of solar heaters